2009
DOI: 10.1021/ol900579k
|View full text |Cite
|
Sign up to set email alerts
|

Biselyngbyaside, a Macrolide Glycoside from the Marine Cyanobacterium Lyngbya sp.

Abstract: Bioassay-guided fractionation of the cytotoxic constituents of the marine cyanobacterium Lyngbya sp. led to the isolation of biselyngbyaside (1), a new 18-membered macrolide glycoside. The structure of 1 was established by spectroscopic analysis including 2D-NMR techniques and by synthetic studies. Biselyngbyaside (1) exhibits broad-spectrum cytotoxicity in a human tumor cell line panel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 14 publications
1
56
0
Order By: Relevance
“…It has been reported that Biselyngbyaside is a potent inhibitor of Ca 2+ pump with unique binding capacity (Teruya et al, 2009;Morita et al, 2015). It has an inhibitory effect on primary bone marrow macrophages as well as RANKL induced osteoclastogenesis in murine RAW 264.7 cells at low concentrations and also suppresses osteoblast-mediated osteoclast differentiation in cocultures.…”
Section: Marine Cyanobacteriamentioning
confidence: 99%
“…It has been reported that Biselyngbyaside is a potent inhibitor of Ca 2+ pump with unique binding capacity (Teruya et al, 2009;Morita et al, 2015). It has an inhibitory effect on primary bone marrow macrophages as well as RANKL induced osteoclastogenesis in murine RAW 264.7 cells at low concentrations and also suppresses osteoblast-mediated osteoclast differentiation in cocultures.…”
Section: Marine Cyanobacteriamentioning
confidence: 99%
“…8 Cryptophycin-309 and cryptophycin-249, synthetic analogs of terrestrial cyanobacterial peptide cryptophycin-1, have undergone preclinical efficacy studies, and there is sufficient interest to consider entering them into a clinical trial. 9 In our ongoing efforts to identify novel marine cyanobacterial metabolites with antitumor activity, 10 we isolated bisebromoamide (1), 11 which shows antiproliferative activity at nanomolar levels, from a cyanobacterium of the genus Lyngbya. Recently, Tao and coworkers achieved synthesis of bisebromoamide, and the stereochemistry of thiazoline moiety was revised.…”
Section: Introductionmentioning
confidence: 99%
“…8 In common partial structures from C-3 to C-8 including C-13 and C-14, the most distinguishable feature of 1 H NMR data between the two diastereomers is a coupling constant ( J ) of H-4. While H-4 has two J values as 3.5 and 8.9 Hz which appeared to be a doublet of doublets in a syn conformation, J is 6.0 Hz as a triplet in an anti conformation which corresponds to compound 1 (Fig.…”
mentioning
confidence: 99%
“…S1). 8 Also, every possible rotamer was carefully considered by virtue of the 3 J H,H value, as well as the 1D and 2D NOE correlations (Fig. 2).…”
mentioning
confidence: 99%